Ferritic stainless steel and ferritic stainless steel welded structure
Patent Information
- Application Number
- JP2023128821
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
Smart Images

Figure 2025024602000003 
Figure 2025024602000001 
Figure 2025024602000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel material and a ferritic stainless steel welded structure. [Background technology]
[0002] Ferritic stainless steel materials are inexpensive because they contain no Ni or only a small amount of Ni, but their applications are sometimes limited because they are inferior in corrosion resistance and workability to austenitic stainless steel materials.
[0003] In recent years, the expansion of applications of ferritic stainless steel materials has led to a demand for improved corrosion resistance of ferritic stainless steel materials. In particular, in applications such as building panels and piping, which may be used in outdoor environments (e.g., outdoor corrosive environments such as salt damage environments), weather resistance is required. Examples of weather resistance include the inhibition of rusting in outdoor environments and the inhibition of holes caused by corrosion.
[0004] As a technique for improving the corrosion resistance of ferritic stainless steel materials, a method of adding alloy elements such as Cr and Mo is known. However, in ferritic stainless steel materials, once corrosion (pitting corrosion) has occurred, it progresses faster than in austenitic stainless steel materials, so in order to slow down the rate of corrosion progression, it is necessary to add large amounts of Cr and Mo. However, adding large amounts of Cr and Mo would undermine the advantage of ferritic stainless steel materials, that is, their low cost.
[0005] Furthermore, as a technique for improving the corrosion resistance of ferritic stainless steel materials (raw materials), a method for controlling the amount of added Si is known (for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2019-112709 A [Patent Document 2] JP 2018-165384 A [Patent Document 3] JP 2010-229470 A [Patent Document 4] JP 2020-164937 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, improving weather resistance cannot be expected by controlling the amount of Si added. In fact, the addition of Si is effective in improving corrosion resistance in neutral environments, but has almost no effect in inhibiting the progress of corrosion in outdoor environments (especially in low pH environments). In addition, the addition of Si hardens the ferritic stainless steel material, which tends to reduce the toughness of the weld metal when it is welded. Although the toughness of the weld metal can be ensured by increasing the amount of Ni added, adding a large amount of Ni reduces the advantage of ferritic stainless steel, which is that it is inexpensive.
[0008] The present invention has been made to solve the above-mentioned problems, and has an object to provide a ferritic stainless steel material that has excellent weather resistance and excellent toughness of the weld metal part when welded. Another object of the present invention is to provide a ferritic stainless steel welded structure having excellent weather resistance and toughness of a weld metal part. [Means for solving the problem]
[0009] In order to solve the above problems, the present inventors have conducted extensive research into ferritic stainless steel materials and have discovered that by controlling the composition and the proportion of specific S-based inclusions, not only weather resistance but also the toughness of the welded metal joint when welded can be improved, thereby completing the present invention.
[0010] That is, the present invention relates to a steel sheet having, on a mass basis, C: 0.020% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.020% or less, the total of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, and the balance being Fe and impurities, and has the following formulas (1) to (3): Al+10Ca+Mg≦0.200 (1) Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0 (2) C+N≦0.020% (3) (wherein each element symbol represents the content of each element), The number ratio of S-based inclusions with a diameter equivalent size of 1 μm or more and an S content of 1 mass% or more is 15.0 pieces / mm 2 The following ferritic stainless steel material is used.
[0011] The present invention also provides a ferritic stainless steel welded structure having a base material and a weld metal part, The base material is a ferritic stainless steel welded structure that is a ferritic stainless steel material. Effect of the Invention
[0012] According to the present invention, it is possible to provide a ferritic stainless steel material that is excellent in weather resistance and in toughness of the weld metal part when welded. Furthermore, according to the present invention, it is possible to provide a ferritic stainless steel welded structure having excellent weather resistance and toughness of the weld metal part. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic partially enlarged cross-sectional view of a ferritic stainless steel welded structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0015] The ferritic stainless steel material according to an embodiment of the present invention contains C: 0.020% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.020% or less, the total of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, with the balance being Fe and impurities.
[0016] Here, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape. In addition, in this specification, "ferritic" means that the metal structure is mainly ferritic phase at room temperature. Therefore, "ferritic" also includes those that contain small amounts of phases other than ferritic phase (e.g., austenite phase, martensite phase, etc.). However, "ferritic" does not include a multi-phase structure of ferritic phase and austenite phase, a multi-phase structure of ferritic phase and martensite phase, or a multi-phase structure of ferritic phase, austenite phase, and martensite phase.
[0017] In addition, in this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of ferritic stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. An example of an impurity is O. With regard to the content of each element, "xx% or less" means that the content is xx% or less, but includes an amount exceeding 0% (particularly, exceeding the impurity level).
[0018] The ferritic stainless steel material according to an embodiment of the present invention may further contain, as necessary, one or more selected from Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less. Each component will be described in detail below.
[0019] (C: 0.020% or less) C is an element that affects the properties of ferritic stainless steel materials (hereinafter sometimes abbreviated as "stainless steel materials"), such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the C content is too high, the workability and weather resistance of the stainless steel material will decrease. In addition, if the C content is too high, the amount of precipitates (Ti carbonitrides, Nb carbonitrides, etc.) generated will increase, and the toughness of the weld metal part when the stainless steel material is welded will decrease. Therefore, the upper limit of the C content is 0.020%, preferably 0.015%, and more preferably 0.010%. On the other hand, the lower limit of the C content is not particularly limited, but excessively reducing the C content leads to an increase in refining costs. Therefore, the lower limit of the C content is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%.
[0020] (Si: 1.00~3.00%) Si is an element effective in improving the properties of stainless steel materials, such as oxidation resistance, mechanical strength, and weather resistance. Among these properties, from the viewpoint of improving weather resistance (for example, pitting corrosion resistance in a neutral environment such as salt water), the lower limit of the Si content is 1.00%, preferably 1.05%, and more preferably 1.10%. On the other hand, if the Si content is too high, it acts as a solid solution strengthening element, which reduces the workability and reduces the toughness of the weld metal when the stainless steel material is welded. Therefore, the upper limit of the Si content is 3.00%, preferably 2.90%, and more preferably 2.80%.
[0021] (Mn:1.00% or less) Mn is an element effective for fixing S (desulfurization). However, if the Mn content is too high, MnS, which is the starting point of corrosion, is easily generated and the ferrite phase is destabilized. Therefore, the upper limit of the Mn content is 1.00%, preferably 0.80%, and more preferably 0.50%. On the other hand, the lower limit of the Mn content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect of Mn, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.05%.
[0022] (Ni: 1.00% or less) Ni is an element effective in improving the weather resistance of stainless steel materials, and has the effect of suppressing the progression of pitting corrosion and crevice corrosion in a low pH environment in particular. However, if the Ni content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the Ni content is 1.00% or less, preferably 0.80% or less, more preferably 0.50% or less, even more preferably 0.30% or less, and particularly preferably less than 0.20%. On the other hand, the lower limit of the Ni content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%.
[0023] (P:0.100% or less) P is an element that affects the properties of stainless steel materials, such as weldability and workability. However, if the P content is too high, the above properties may be deteriorated, so the upper limit of the P content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the P content is not particularly limited, but an excessively low P content leads to an increase in refining costs. Therefore, the lower limit of the P content is preferably 0.001%, more preferably 0.005%, and even more preferably 0.008%.
[0024] (S:0.0020% or less) S is an element that generates S-based inclusions such as MnS, which are the starting point of corrosion, and affects the weather resistance of stainless steel materials and the toughness of the weld metal when the stainless steel material is welded. In particular, if the S content is too high, the above-mentioned properties are reduced, so it is necessary to reduce the S content and the number of S-based inclusions in the stainless steel material. Therefore, the upper limit of the S content is 0.0020%, preferably 0.0019%, and more preferably 0.0018%. On the other hand, the lower limit of the S content is not particularly limited, but excessively reducing the S content leads to an increase in refining costs. Therefore, the lower limit of the S content is preferably 0.0001%, and more preferably 0.0002%.
[0025] (Cr:13.00~32.00%) Cr is an element effective in improving the corrosion resistance and oxidation resistance of stainless steel materials. In particular, from the viewpoint of ensuring weather resistance in consideration of outdoor salt damage environments, the lower limit of the Cr content is 13.00%, preferably 14.00%, and more preferably 15.00%. On the other hand, if the Cr content is too high, the manufacturing cost increases and it becomes difficult to ensure the toughness of the hot-rolled material, resulting in a decrease in manufacturability. Therefore, the upper limit of the Cr content is 32.00%, preferably 30.00%, and more preferably 25.00%.
[0026] (N:0.020% or less) N is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the N content is too high, the weather resistance and workability of the stainless steel material will decrease. In addition, if the N content is too high, the amount of precipitates (Ti carbonitrides, Nb carbonitrides, etc.) generated will increase, and the toughness of the weld metal part when the stainless steel material is welded will decrease. Therefore, the upper limit of the N content is 0.020%, preferably 0.018%, and more preferably 0.015%. On the other hand, the lower limit of the N content is not particularly limited, but excessively reducing the N content leads to an increase in refining costs. Therefore, the lower limit of the N content is preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%.
[0027] (Total of Nb and Ti: 6(C+N)~0.700%) Nb and Ti are elements that affect the intergranular corrosion resistance (sensitization suppression effect) of stainless steel materials. In addition, since Nb and Ti are elements that are effective in fixing C and N, the total content of Nb and Ti is determined based on the amount of C and N. That is, the lower limit of the total content of Nb and Ti is 6(C+N)% from the viewpoint of obtaining the above-mentioned effect. However, if the total content of Nb and Ti is too high, in addition to increasing the manufacturing cost, the workability and surface quality of the stainless steel material are deteriorated. Therefore, the upper limit of the total content of Nb and Ti is 0.700%, preferably 0.600%, and more preferably 0.500%. In addition, the individual contents of Nb and Ti are not particularly limited, but from the viewpoint of suppressing the coarsening of crystal grains during bright annealing, each is preferably 0.05% or more, more preferably 0.06% or more. In particular, Nb forms carbonitrides such as NbC and NbN, and the pinning effect of these carbonitrides can effectively suppress the coarsening of crystal grains.
[0028] (Cu:2.00% or less) Cu is an element effective in improving the workability and weather resistance of stainless steel materials. In particular, Cu has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Cu content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Cu content is 2.00%, preferably 1.50%, and more preferably 1.00%. On the other hand, the lower limit of the Cu content is not particularly limited, but is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%, from the viewpoint of obtaining the effect of Cu.
[0029] (Mo: 2.50% or less) Mo is an element effective in improving the weather resistance and oxidation resistance of stainless steel materials. In particular, Mo has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Mo content is too high, it leads to a decrease in the workability of the stainless steel material and an increase in the manufacturing cost. Therefore, the upper limit of the Mo content is 2.50%, preferably 2.00%, and more preferably 1.50%. On the other hand, the lower limit of the Mo content is not particularly limited, but from the viewpoint of obtaining the effect of Mo, it is preferably 0.01%, more preferably 0.03%, and even more preferably 0.05%.
[0030] (Al: 0.010~0.150%) Al is an extremely effective element as a deoxidizing element. In particular, Al forms oxides together with Si, reducing O (oxygen) in the parent phase. However, if the Al content is too high, the amount of oxides increases, and it is easy to form water-soluble inclusions by combining with sulfides. These inclusions become the starting point of corrosion and reduce the weather resistance of the stainless steel material. They also cause a decrease in the toughness and weldability of the stainless steel material. Therefore, the upper limit of the Al content is 0.150%, preferably 0.130, and more preferably 0.100%. On the other hand, the lower limit of the Al content is 0.010%, preferably 0.015%, and more preferably 0.020%, from the viewpoint of ensuring the deoxidizing effect of Al.
[0031] (Ca:0.0100% or less) Ca is an extremely effective element as a deoxidizing element. In particular, Ca forms oxides together with Si and reduces O (oxygen) in the parent phase. Ca is also an element that improves hot workability and cleanliness of stainless steel materials. However, if the Ca content is too high, oxides and sulfides are easily formed, and in particular, sulfides (CaS) are soluble in water, which can be the starting point of corrosion and reduce the weather resistance of stainless steel materials. Therefore, the upper limit of the Ca content is 0.0100%, preferably 0.0090%, and more preferably 0.0080%. On the other hand, the lower limit of the Ca content is not particularly limited, but from the viewpoint of ensuring the effect of Ca, it is preferably 0.0003%, more preferably 0.0005%, and even more preferably 0.0010%.
[0032] (Mg:0.0100% or less) Mg is an extremely effective element as a deoxidizing element. In particular, Mg forms oxides together with Si and reduces O (oxygen) in the parent phase. Mg is also an element that improves hot workability and cleanliness of stainless steel materials. However, if the Mg content is too high, the manufacturability of stainless steel materials decreases, and the amount of oxides increases, which combine with sulfides to form inclusions soluble in water, which become the starting point of corrosion and reduce the weather resistance of stainless steel materials. Therefore, the upper limit of the Mg content is 0.0100%, preferably 0.0080%, and more preferably 0.0060%. On the other hand, the lower limit of the Mg content is not particularly limited, but is 0.0001%, more preferably 0.0003%, and even more preferably 0.0005% from the viewpoint of ensuring the effect of Mg.
[0033] (O: 0.004% or less) O forms oxides with other additive elements. When sulfides aggregate on such oxides, they act as water-soluble inclusions that become corrosion initiation sites, leading to a decrease in the weather resistance of the stainless steel material. Therefore, the upper limit of the O content is set to 0.004%, preferably 0.003%, and more preferably 0.002%. On the other hand, an excessive reduction in O leads to an increase in raw material and refining costs, so the lower limit of the O content is preferably 0.0001%, and more preferably 0.0005%.
[0034] (Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less) Zr, Co, V and W are elements effective for improving the oxidation resistance of stainless steel materials. However, if the content of Zr, Co, V and W is too high, the workability and toughness of the stainless steel material will decrease, and the manufacturing cost will increase. Therefore, the upper limit of the content of Zr, Co, V and W is 1.00%, preferably 0.95%, and more preferably 0.90%. On the other hand, the lower limit of the content of Zr, Co, V and W is not particularly limited, but is preferably 0.001%, and more preferably 0.01%.
[0035] (REM: 0.100% or less) REM is an element effective in improving the oxidation resistance of stainless steel materials. However, if the REM content is too high, it leads to an increase in manufacturing costs. Therefore, the upper limit of the REM content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the REM content is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%. In addition, REM is a general term for 17 elements in total, including Sc, Y, and lanthanoids, and refers to rare earth metals. Specifically, La, Ce, Nd, etc. can be mentioned, and one of these can be contained alone or two or more can be contained in combination. When two or more rare earth elements are contained, the above-mentioned REM content means the total content of these rare earth elements.
[0036] (Sn:0.100% or less) Sn is an element effective for improving the oxidation resistance of stainless steel materials. However, if the Sn content is too high, Sn segregates and the manufacturability of stainless steel materials decreases. Therefore, the upper limit of the Sn content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the Sn content is not particularly limited, but is preferably 0.001%, and more preferably 0.002%.
[0037] (B:0.0100% or less) B is an element effective for improving the secondary workability of stainless steel materials. However, if the B content is too high, the fatigue strength of the stainless steel material decreases. Therefore, the upper limit of the B content is 0.0100%, preferably 0.0090%, and more preferably 0.0080%. On the other hand, the lower limit of the B content is not particularly limited, but is preferably 0.0001%, and more preferably 0.0003%.
[0038] The ferritic stainless steel material according to the embodiment of the present invention satisfies the following formula (1). Al+10Ca+Mg≦0.200 (1) In formula (1), each element symbol represents the content of each element. Formula (1) is related to the proportion of the number of specific S-based inclusions described below, and by satisfying the conditions of formula (1), it becomes easier to reduce the proportion of the number of the specific S-based inclusions. Al, Ca, and Mg used in the calculation based on the element contents in formula (1) are elements related to S-based inclusions formed by the aggregation of S (sulfur) or sulfides. In particular, Al and Mg form oxides, and aggregate with S or sulfides to form S-based inclusions. Ca has a higher tendency to form oxides than Al and Mg, and also a higher tendency to combine with S to form sulfides. As a result of intensive research, it was found that Ca has a 10 times higher tendency to contribute to the formation of S-based inclusions than Al and Mg, and formula (1) was derived.
[0039] The ferritic stainless steel material according to the embodiment of the present invention satisfies the following formula (2). Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0 (2) In formula (2), each element symbol represents the content of each element. Formula (2) is related to the pitting corrosion resistance of stainless steel materials, and by satisfying the conditions of formula (2), it becomes easier to ensure the weather resistance of stainless steel materials in outdoor environments. In a corrosive environment containing halogen ions such as chloride ions, the passive film of stainless steel materials may be locally destroyed by these ions, causing pitting corrosion. The occurrence and progression of this pitting corrosion varies greatly depending on the elements contained in the stainless steel material. In general, the pitting corrosion index (PI=Cr+3Mo) based on Cr has been known as an index of the pitting corrosion resistance of stainless steel materials. In the present invention, however, it was found that Si, Cu, and Ni have an effect on the progression of pitting corrosion in low pH environments such as crevice environments such as gaps and inside pits, and formula (2) was derived.
[0040] Specifically, we derived equation (2) as follows. First, pitting potential measurement was adopted as a method for easily evaluating the pitting corrosion resistance of stainless steel material, and attention was paid to Cr, Mo, as well as Si, Cu, and Ni contained in stainless steel material, to examine the effects of these elements on the pitting corrosion resistance of stainless steel material. The pitting potential measurement was performed in accordance with JIS G0577:2014, and the current value was 100 μA / cm in a 3.5 mass% NaCl aqueous solution at 30°C. 2 The potential exceeding this limit was defined as the pitting potential V'c100. In the stainless steel material according to the embodiment of the present invention, when the material contains 1.00% or more Si, the pitting potential is improved not only by increasing Cr but also by increasing Si, and the effect is 1.7 times that of Cr. The mechanism that brings about this effect is not necessarily clear, but it is presumed from various analyses that the oxide of Si that is generated in the inner layer of the passive film and at the interface between the passive film and the ferritic stainless steel material exhibits an effect of suppressing the destruction of the passive film by halogen ions, particularly in a neutral solution environment such as salt water. In addition, when Mo is contained, the effect is 1.2 times that of Cr. Furthermore, when Cu and Ni are contained, the effect is 0.4 times that of Cr. Based on these findings, in the present invention, the calculation formula (2) was derived as Cr+1.7Si+1.2Mo+0.4(Cu+Ni).
[0041] Here, the pitting potential V'c100 of the stainless steel material according to the embodiment of the present invention was compared with the pitting potential V'c100 of SUS430J1L (19Cr ferritic stainless steel material), SUS443J1 (21Cr ferritic stainless steel material), and SUS304 (18Cr-8Ni austenitic stainless steel material). As a result, in the present invention, by making the value of formula (2) exceed 19.0, it was possible to achieve a pitting potential of 0.20V equivalent to SUS430J1L. Also, in the present invention, by making the value of formula (2) 21.0 or more, it was possible to achieve a pitting potential of 0.30V equivalent to SUS443J1 and SUS304. Therefore, in the present invention, the value of formula (2) is set to exceed 19.0. The upper limit of the value of formula (2) is not particularly limited, but if it is too high, the Si content tends to be too high, which increases the tensile strength and hardness, reduces the workability, and increases the manufacturing cost. Similarly, if the Mo, Cu, and Ni contents are high, the raw material cost increases. Therefore, the upper limit of formula (2) is preferably 25.0.
[0042] The ferritic stainless steel material according to the embodiment of the present invention satisfies the following formula (3). C+N≦0.020% (3) In formula (3), each element symbol represents the content of each element. When stainless steel materials are welded, the weld metal portion is heated to a high temperature, so that Ti carbonitrides and Nb carbonitrides contained in the stainless steel material are solid-dissolved. In this case, if the weld metal portion is quenched after welding, the amount of solid-dissolved C and N becomes large, and the weld metal portion becomes hard. Conversely, if the weld metal portion is slowly cooled after welding, a large amount of coarse precipitates (Ti carbonitrides and Nb carbonitrides) precipitate. Both of these conditions are factors that reduce the toughness of the weld metal portion. Therefore, by controlling C+N (the total amount of C and N) to 0.020% or less, the weld metal portion is prevented from hardening and the coarse precipitates are prevented from being generated. In addition, by controlling in this manner, the toughness of the weld metal portion can be ensured regardless of the welding method or the cooling conditions after welding. From the viewpoint of stably ensuring these effects, C+N is preferably 0.019% or less, and more preferably 0.018% or less.
[0043] The ferritic stainless steel material according to the embodiment of the present invention has a ratio of the number of S-based inclusions having a diameter equivalent size of 1 μm or more and an S content of 1% or more of 15.0 pieces / mm 2 The following is the result. In this specification, the term "S-based inclusions" refers to inorganic compounds containing S, which are formed during the steelmaking process. S-based inclusions contain sulfides such as MnS and CaS. In addition to sulfides formed alone, S-based inclusions may also be formed by agglomeration of Al, Ca, and Mg oxides together with the sulfides.
[0044] S-based inclusions dissolve in water in a corrosive environment, forming gaps between the stainless steel base material and the material. A potential difference occurs inside the gap, which not only drives corrosion, but also dissolves metal ions from the base material when pitting occurs in the gap. The dissolved Cr ions form hydrates, lowering the pH of the surrounding environment. This tendency is particularly strong in gaps below S-based inclusions, where ion diffusion is difficult, and repassivation is difficult, leading to the progression of pitting corrosion. Ferritic stainless steels with low Ni content corrode faster than austenitic stainless steels, so S-based inclusions become corrosion initiation points. It is therefore necessary to reduce the number of S-based inclusions of a specific size that act as corrosion initiation points.
[0045] Among S-based inclusions, S-based inclusions with a diameter equivalent size of 1 μm or more and an S content of 1% or more (hereinafter referred to as "specific S-based inclusions") tend to become corrosion initiation points. Therefore, the number ratio of these specific S-based inclusions is set to 15.0 pieces / mm 2 By controlling the number of specific S-based inclusions below 13.0 pieces / mm, corrosion of stainless steel materials can be suppressed. 2 It is preferable that the number of pieces is 10.0 pieces / mm or less. 2 It is more preferable that the ratio of the number of the specific S-based inclusions is not particularly limited, since the smaller the ratio, the better.
[0046] The specific S-based inclusion is an S-based inclusion having a diameter equivalent size of 1 μm or more. Here, the "diameter equivalent size" refers to the value obtained by raising the product of the long side dimension and the short side dimension of the shape to the power of 1 / 2 ((long side × short side) 1 / 2 ) This means that even if the shape of the S-based inclusion is irregular, its size can be unambiguously determined. In addition, S-based inclusions with a diameter equivalent size of less than 1 μm are so small that they are unlikely to generate a potential difference between the inside and outside of the gap, which is the driving force for corrosion, and diffusion is likely to occur even when pitting corrosion occurs in the gap. Therefore, since the decrease in pH is only slight, they are unlikely to become the starting point of corrosion. In addition, S-based inclusions with an S content of less than 1% are unlikely to dissolve and form gaps between the base material and the inclusions, and therefore are unlikely to become corrosion initiation points. Therefore, even if S-based inclusions are present near the surface of stainless steel materials, the number ratio of specific S-based inclusions with a diameter equivalent size of 1 μm or more and an S content of 1% or more is set to 15.0 pieces / mm 2 Weather resistance can be improved by the following.
[0047] Here, the number ratio of the specific S-based inclusions is measured by polishing the surface of the stainless steel material to remove surface irregularities, mirror-finishing it, and observing it as follows: First, the inclusions are detected using an FE-SEM (field emission scanning electron microscope: SU-5000, manufactured by Hitachi High-Tech Corporation) device, and the composition of the specific inclusions is measured by further point-analyzing the parts with an EDX (energy dispersive X-ray analysis) device. Next, among the detected inclusions, the number of specific S-based inclusions having a diameter equivalent size of 1 μm or more and an S content of 1% or more as determined by EDX component analysis is determined. The number of specific S-based inclusions is then divided by the observation area to calculate the number ratio.
[0048] The method for producing the ferritic stainless steel material according to the embodiment of the present invention is not particularly limited as long as it can produce a ferritic stainless steel material having the above-mentioned characteristics. A preferred method for producing the ferritic stainless steel material according to the embodiment of the present invention will be described below. In the manufacturing method of the ferritic stainless steel material according to the embodiment of the present invention, the S content is reduced by increasing the refining time and reducing the scrap ratio. In the conventional method, it is common to reduce S by extending the refining time in a converter. On the other hand, in order to regulate the extremely small S content, the extension of the refining time alone significantly impairs manufacturability, and in practice, the manufacturing cost increases, so it is not implemented in practice. The reduction of the S content in the ferritic stainless steel material according to the embodiment of the present invention can be achieved not only by extending the refining time, but also by reducing the scrap ratio, which is the main cause of the inclusion of impurities such as S. The scrap ratio is not particularly limited, but is preferably 40% or less, and more preferably 35% or less.
[0049] The stainless steel obtained by refining can be processed into various shapes by a conventional method. For example, the stainless steel can be made into a rolled material by performing a rolling process. Examples of the rolled material include hot-rolled material and cold-rolled material. For example, the cold-rolled material can be produced by performing hot rolling, annealing, and pickling on the stainless steel, followed by cold rolling. After the cold rolling, various treatments (annealing, pickling, polishing, etc.) may be performed. The conditions of the rolling process and the like are not particularly limited, and can be set in accordance with conventional methods.
[0050] The ferritic stainless steel material according to the embodiment of the present invention manufactured as described above has excellent weather resistance and excellent toughness of the welded metal when welded, and can be used in various applications where these properties are required, such as building materials such as building panels, piping, etc.
[0051] A ferritic stainless steel welded structure according to an embodiment of the present invention has a base material and a weld metal part. The base material is the above-mentioned ferritic stainless steel material. FIG. 1 shows a schematic enlarged partial cross-sectional view of a ferritic stainless steel welded structure. As shown in Figure 1, the ferritic stainless steel welded structure (100) includes a base material (10) and a weld metal portion (30). The ferritic stainless steel welded structure (100) further includes a heat-affected zone (20) between the base material (10) and the weld metal portion (30). Here, "base material" refers to the part that is not affected by welding. "Heat-affected zone" refers to the part that is affected by heat but does not melt due to welding (also called HAZ). "Weld metal zone" refers to the part that melts and resolidifies due to welding.
[0052] The difference between the Vickers hardness of the base metal and the Vickers hardness of the weld metal part is preferably 30 HV or less, more preferably 25 HV or less, and even more preferably 20 HV or less. If the Vickers hardness difference is within this range, the weld metal part is not hardened and the toughness of the weld metal part is ensured. The lower limit of this Vickers hardness difference is not particularly limited, and the smaller the better. The Vickers hardness can be measured using a Vickers hardness tester.
[0053] The total number of inclusions and precipitates with a diameter equivalent size of 1 μm or more in the weld metal is 30.0 pieces / mm 2 It is preferable that the number of pieces is 25.0 pieces / mm or less. 2 More preferably, it is 20.0 pieces / mm or less. 2 It is more preferable that the total number ratio is within this range. If the total number ratio is within this range, it can be said that the amount of inclusions and precipitates having a diameter equivalent size of 1 μm or more, which cause a decrease in the toughness of the weld metal part, is small. The lower limit of this total number ratio is not particularly limited, since the smaller the better. The equivalent diameter size has the same meaning as defined above.
[0054] The total number ratio of inclusions and precipitates in a weld metal part is measured by mirror-finishing the surface of the weld metal part and observing it as follows. First, inclusions and precipitates are detected using a FE-SEM (field emission scanning electron microscope: SU-5000 manufactured by Hitachi High-Tech Corporation) device, and the number of inclusions and precipitates detected that have a diameter equivalent size of 1 μm or more is determined. The total number of inclusions and precipitates that have a diameter equivalent size of 1 μm or more is then divided by the observation area to calculate the number ratio.
[0055] The ferritic stainless steel welded structure according to the embodiment of the present invention can be manufactured by welding ferritic stainless steel materials having the above-mentioned characteristics. The welding method is not particularly limited, and known methods such as arc welding (TIG welding, etc.), electron beam welding, laser welding, plasma arc welding, and spot welding can be used. The welding conditions are not particularly limited and may be appropriately adjusted according to the welding method. In particular, the ferritic stainless steel material used for welding has a total amount of C and N controlled to 0.020% or less, so that the hardening of the weld metal part and the generation of coarse precipitates can be suppressed regardless of the cooling rate after welding. It is preferable not to use a filler metal for welding.
[0056] The ferritic stainless steel welded structure according to the embodiment of the present invention produced as described above has excellent weather resistance and toughness of the weld metal, and can be used in various applications where these properties are required, such as building materials such as building panels, piping, etc. EXAMPLES
[0057] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0058] Stainless steel having the composition shown in Table 1 (the balance being Fe and impurities) was melted and hot rolled to obtain a hot rolled sheet having a thickness of 3.0 mm, which was then annealed at 1050°C and pickled to obtain a hot rolled annealed sheet. Next, the hot rolled annealed sheet was cold rolled to obtain a cold rolled sheet having a thickness of 1.0 mm, which was then annealed at 1000°C for 1 minute in an air atmosphere and pickled to obtain a ferritic stainless steel sheet. Next, a stainless steel sheet sample of 300 mm (rolling direction) x 100 mm (width direction) was cut out from the obtained ferritic stainless steel sheet.
[0059] [Table 1]
[0060] In addition, the rolling direction end faces of the two stainless steel plate samples obtained above were smoothed by cutting, and then the end faces were butted together and TIG welded to obtain a stainless steel welded structure sample. The TIG welding was performed with an electrode diameter of 1.6 mm, a current value of 90 A, and a welding speed of 0.5 mm / min. After welding, the samples were quenched by blowing Ar gas at a rate of 15 L / min, or slowly cooled without blowing Ar gas. Note that no filler metal was used in the TIG welding.
[0061] The following evaluations were carried out for each of the samples obtained above.
[0062] (Number ratio of specific S-type inclusions) A test piece of 10 mm (rolling direction) x 10 mm (width direction) was cut out from the above stainless steel plate sample by cutting. The sample was cut out at a position 20 mm or more away from the end in the width direction. Next, the surface of the stainless steel plate was filled with resin so that it would be the observation surface, and then polished to remove surface irregularities, and finally wet polished to a mirror finish. After that, inclusions were detected using an FE-SEM (SU-5000, manufactured by Hitachi High-Tech Corporation) device, and the composition of specific inclusions was measured by EDX point analysis. Note that this measurement was performed using the automatic inclusion analysis function of the device, and the conditions are as follows. Measurement range: Measurement area 5mm 2 (2.0mm x 2.5mm) Observation magnification: 200 times (1 visual field range 0.48 mm × 0.64 mm) with 5% overlap, 18 visual fields were measured to obtain the above measurement range. The minimum detectable particle diameter was 0.47 μm. EDX analysis beam diameter: 0.05 μm Among the detected inclusions, the number of specific S-based inclusions with a diameter equivalent size of 1 μm or more and an S content of 1% or more as determined by EDX component analysis was determined. The number of specific S-based inclusions was divided by the observation area to obtain the number ratio (pieces / mm 2 ) was calculated.
[0063] (Total number ratio of specific inclusions and precipitates in weld metal) A test piece measuring 10 mm (rolling direction) x 10 mm (width direction) was cut out from the above stainless steel welded structure sample by cutting so that the weld metal part was located at the center in the width direction. Next, resin was filled in so that the surface of the weld metal part would be the observation surface, and then it was mirror-finished by wet polishing (grinding amount: approximately 50 μm). After that, inclusions and precipitates were detected using an FE-SEM (SU-5000, manufactured by Hitachi High-Tech Corporation), and the total number of inclusions and precipitates with a diameter equivalent size of 1 μm or more was determined. The total number of inclusions and precipitates obtained was then divided by the observation area to determine the number ratio (pieces / mm 2 The other measurement conditions were the same as those for the measurement of the number ratio of the specific S-based inclusions described above. In this evaluation, the total number rate is 30.0 pieces / mm 2 If this is the case, it can be said that the amount of inclusions and precipitates having a diameter equivalent size of 1 μm or more, which cause a decrease in the toughness of the weld metal, is small.
[0064] (Difference between the Vickers hardness of the base material and the Vickers hardness of the weld metal) A test piece of 25 mm (rolling direction) x 25 mm (width direction) was cut out from the above stainless steel welded structure sample by cutting so that the weld metal part was in the center of the width direction. Next, resin filling was performed so that the thickness direction cross section was the observation surface. Next, the resin-filled test piece was mirror-finished by wet polishing using SiC polishing paper and diamond paste. Then, the Vickers hardness of the base material and the weld metal part was measured using a micro Vickers hardness tester. In this measurement, the load was 0.01 kg, and measurements were performed at any five points, and the average value was taken as the result. The Vickers hardness of the base material was measured at a position 5 mm or more away from the position where the Vickers hardness of the weld metal part was measured. From the obtained Vickers hardness of the base material and the weld metal part, the difference between the Vickers hardness of the base material and the Vickers hardness of the weld metal part was calculated. In this evaluation, if the difference in Vickers hardness is 30 HV or less, it can be said that the weld metal part has not hardened and the toughness of the weld metal part is ensured.
[0065] (Toughness of weld metal) The toughness of the weld metal was evaluated by bending as follows. A test specimen having a width of 50 mm and a length of 10 mm was cut out from the above stainless steel welded structure sample so that the weld metal part was located at the center and parallel to the length direction. Next, a universal testing machine was used to perform 2T bending at room temperature so that the longitudinal direction of the weld metal part was perpendicular to the bending ridge line. The 2T bending process is a process in which the test specimen is bent 180° with two plates having the same thickness as the test specimen sandwiched inside the bending direction of the test specimen. In this bending process, the test specimens that did not crack in the weld metal part were judged as ○ (good toughness), and the test specimens that cracked in the weld metal part were judged as × (poor toughness).
[0066] (weather resistance) Weather resistance was evaluated by a salt, dry and wet combined cycle test. A test piece of 100 mm (rolling direction) x 50 mm (width direction) was cut out from the above stainless steel plate sample, and three sides of the test piece (except one side in the width direction) were covered with resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, two polyethylene tubes of 20 mmφ x 10 mm were bonded onto a Bakelite plate of 70 mm x 150 mm, and the side of the test piece not covered with resin was placed on top of the tubes and bonded. A salt-dry-wet combined cycle test (CCT) was performed on the measurement sample obtained in this way. The sample was placed in a CCT device so that the surface of the test piece for measurement was at 75° to the horizontal plane and the side of the test piece for measurement that was not covered with resin was at the bottom, and four cycles were performed, each consisting of 5% salt spray (35°C, 2 hours), drying (60°C, 25% RH, 4 hours), and wetting (50°C, 95% RH, 2 hours). The measurement samples were then washed with water and dried, and the rust area ratio on the surface of the test pieces was evaluated (based on JIS G0595:2004). In this evaluation, if the rating number (RN) is 8.0 or higher (corresponding to a rust area ratio of 0.25% or less), it can be determined that the weather resistance is good.
[0067] The above evaluation results are shown in Table 2.
[0068] [Table 2]
[0069] As shown in Table 2, the ferritic stainless steel sheets of Examples 1 to 5 had compositions and proportions of specific S-based inclusions within appropriate ranges, and therefore had good weather resistance and weld metal toughness. In contrast, the ferritic stainless steel sheet of Comparative Example 1 had an excessively large total amount of C and N, which increased the amount of solid solution of C and N during rapid cooling after welding, hardening the weld metal zone. As a result, the difference between the Vickers hardness of the base material and the Vickers hardness of the weld metal zone became large, and the toughness of the weld metal zone could not be ensured. The ferritic stainless steel sheet of Comparative Example 2 also had too much total amount of C and N, so many coarse precipitates (Ti carbonitrides and Nb carbonitrides) precipitated during slow cooling after welding, which resulted in a high ratio of the total number of inclusions and precipitates with a diameter equivalent size of 1 μm or more in the weld metal zone, making it impossible to ensure the toughness of the weld metal zone. The ferritic stainless steel sheet of Comparative Example 3 had too much S content and too little total amount of Nb and Ti, resulting in a high ratio of specific S-based inclusions and failing to ensure weather resistance. In addition, this ferritic stainless steel sheet also had too much C content and too much total amount of C and N, resulting in the precipitation of many coarse precipitates (Ti carbonitrides and Nb carbonitrides) during slow cooling after welding, resulting in a high ratio of the total number of inclusions and precipitates with a diameter equivalent size of 1 μm or more in the weld metal zone, and failing to ensure toughness of the weld metal zone.
[0070] The ferritic stainless steel sheet of Comparative Example 4 did not satisfy the condition of formula (1), and therefore had a high proportion of specific S-based inclusions, and was therefore unable to ensure weather resistance. Furthermore, in this ferritic stainless steel sheet, the specific S-based inclusions did not disappear during welding, and the total proportion of inclusions and precipitates with a diameter equivalent size of 1 μm or more in the weld metal zone was also high, and therefore the toughness of the weld metal zone could not be ensured. The ferritic stainless steel sheet of Comparative Example 5 had too little Al content and too much O content, resulting in a high proportion of specific S-based inclusions and failing to ensure weather resistance. The ferritic stainless steel sheet of Comparative Example 6 had too little Si content and did not satisfy the condition of formula (2), so weather resistance could not be ensured. The ferritic stainless steel sheet of Comparative Example 7 had too little Cr content and did not satisfy the condition of formula (2), so weather resistance could not be ensured.
[0071] As can be seen from the above results, the present invention can provide a ferritic stainless steel material that is excellent in weather resistance and in toughness of the weld metal when welded. Also, the present invention can provide a ferritic stainless steel welded structure that is excellent in weather resistance and in toughness of the weld metal.
Claims
1. On a mass basis, it contains C: 0.020% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.020% or less, the total of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, the balance being Fe and impurities, and has the following formulas (1) to (3): Al+10Ca+Mg≦0.200...(1) Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0...(2) C+N≦0.020%...(3) (wherein each element symbol represents the content of each element), The number ratio of S-based inclusions having a diameter equivalent size of 1 μm or more and an S content of 1 mass% or more is 15.0 pieces / mm 2 Ferritic stainless steel material having the following properties:
2. The ferritic stainless steel material according to claim 1, further comprising, on a mass basis, one or more selected from Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
3. A ferritic stainless steel welded structure having a base material and a weld metal part, The ferritic stainless steel welded structure according to claim 1 or 2, wherein the base material is the ferritic stainless steel material.
4. 4. The ferritic stainless steel welded structure according to claim 3, wherein the difference between the Vickers hardness of the base metal and the Vickers hardness of the weld metal portion is 30 HV or less.
5. The total number ratio of inclusions and precipitates having a diameter equivalent size of 1 μm or more in the weld metal part is 30.0 pieces / mm 2 The ferritic stainless steel welded structure of claim 3, wherein:
Citation Information
Patent Citations
Welded structure made from stainless steel having superior toughness at weld, and stainless steel sheet to be welded
JP2010229470A
Ferritic stainless steel and welded structure
JP2018165384A
Ferritic stainless steel
JP2019112709A
Ferritic stainless steel
JP2020164937A